Evaluación de la implementación de un reductor de viscosidad en el proceso de tratamiento de crudo de la estación A1 del campo CS-E de la empresa Ecopetrol S.A. (2020)
The present project, the evaluation of the implementation of a viscosity reducer in the crude treatment process in station A1 of the CS-E field of the company Ecopetrol S.A. was proposed. which was initially carried out in the laboratories of the mentioned station, determining the incidence that the viscosity reducing product would have in different concentrations with the direct breaker product that is currently in the field; This is done through compatibility tests (fluid tests and bottle tests) with the use of equipment such as: centrifuge, water bath, oven, laboratory glassware and photographic camera, where the incidence was found to be nil.